2016
DOI: 10.3329/bjvm.v13i2.26628
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Maternally Derived Antibodies in Calves to Vaccination Against Foot and Mouth Disease

Abstract: This study aimed to know the level of maternally derived antibody (MDA) titer in calves born to cows vaccinated with inactivated trivalent (type O, A and Asia 1) Foot and Mouth disease vaccine. Three groups of calves (10 calves in each group) of different age were randomly selected from two organized farms from Savar Upazilla of Bangladesh where the dams are routinely vaccinated with trivalent FMD vaccines. Blood samples were collected from these selected calves in six occasions five weeks apart and sera (n=18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Therefore, the presence of anti-NSP antibodies as well as anti-SP antibodies for FMD virus serotypes 'O,' ' A,' and ' Asia1' in these calves suggests the passive transfer of maternal antibodies via colostrum from immunised dams to their calves. Previous research has shown that maternal antibodies can survive in calves for up to two months after birth [16,17], whereas Akhter., et al [18] found MDA in calves' serum up to the age of 22-23 weeks. The immune response of newborn calves to FMDV depends on vaccine formulation and may or may not be dependent on maternal antibodies [6,7].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the presence of anti-NSP antibodies as well as anti-SP antibodies for FMD virus serotypes 'O,' ' A,' and ' Asia1' in these calves suggests the passive transfer of maternal antibodies via colostrum from immunised dams to their calves. Previous research has shown that maternal antibodies can survive in calves for up to two months after birth [16,17], whereas Akhter., et al [18] found MDA in calves' serum up to the age of 22-23 weeks. The immune response of newborn calves to FMDV depends on vaccine formulation and may or may not be dependent on maternal antibodies [6,7].…”
Section: Discussionmentioning
confidence: 96%
“…Besides, the maternally-derived antibodies against respiratory viruses were believed to be kept for 4–6 months for bovine viral diarrhea virus (BVDV)−1, 3–6 months for BVDV-2, 5–7 months for bovine respiratory syncytial virus, 2–4 months for bovine herpesvirus-1, and 5–6 months for bovine parainfluenza virus-3 [ 4 , 9 , 10 ]. The maternally-derived antibodies against foot and mouth disease virus decreased below the protective level at 27–28 weeks (above 6 months) of age [ 2 ]. Although the longevity of the duration of maternally-derived antibodies varied in each virus, it was assumed that the maternally-derived antibodies against a virus are substantially maintained for 4–7 months in a calf.…”
mentioning
confidence: 99%